Anterior Extrusion of Bone Graft after Posterior Lumbar Interbody Fusion with development Deep Vein Thrombosis: Case Report and Literature review - Panyaamornwat, MD, Thanita; Lee, MD, Jung-Hee; Kang, MD, Kyung Chung; Shin, MD, Sung Joon; Shin, MD, Won Ju; Kim, MD, Ki-Tack (Journal of Southeast Asian Orthopaedics, 2022)
Background: Anterior bone graft extrusion is a very rare complication. Most patients with this type of extrusion are asymptomatic. Only few studies reported with the development of deep vein thrombosis (DVT) due to anterior bone graft extrusion and the detailed about the management. Propose: The propose of this study is to report a patient with anterior bone graft extrusion with development of DVT without revision spinal surgery. Materials and Methods: The authors demonstrated case by describing the patient’s history, physical examination, imaging studies and treatment. We also reviewed and discussed related literatures. Results: The patients with foraminal stenosis and disc extrusion of L4-S1 was performed posterior decompression and posterior lumbar interbody fusion of L4-S1. Postoperatively, the patient developed left thigh pain and swelling. The diagnosis of proximal DVT at left common iliac vein was confirmed by Doppler ultrasound and 3D CT angiography. The patient was treated with intervention; stent insertion at left common iliac vein, balloon dilatation, Inferior vena cava(IVC) filter, thrombectomy, injection of low molecular weight heparin. The patients showed an improvement in the clinical of radicular pain and thigh swelling. Conclusion: Proximal DVT due to anterior bone graft extrusion is a very rare complication. The most important clinical symptoms are thigh swelling and pain. We must recognize patient’s early symptoms and give an early diagnosis due to proximal DVT could be develop pulmonary thromboembolism and lead to death. Furthermore, the revision spinal surgery is more complex and associated with severe complications. This study described the management of DVT with nonsurgical approach, such as thrombectomy, common iliac vein stent, IVC filter insertion with an application of anticoagulants without going through revision spinal surgery.